Optimizing costs and sustainability for gamma knife radiosurgery: A cost and breakeven analysis at India’s largest neurosurgery centre - Nitin Agrawal; Nishant Sharma; Tilotma Jamwal; Kshitija Singh; Vijaydeep Siddharth; Sidhartha Satpathy (PLoS ONE, 2025)
Background Establishing and maintaining gamma knife facility incurs significant costs, mandating healthcare institutions to meticulously assess financial implications for sustainability. Methods This study explores the financial implications of setting up and operating a Gamma Knife facility, with an aim to ascertain user charges for achieving breakeven. The study was conducted from January to June 2019 at the largest neurosurgery centre of an Institute of National Importance (INI), in Delhi, India. Applying both Traditional and Time-Driven Activity-Based Costing (TD-ABC) methodologies, capital and operating expenses were calculated. (1US$ = INR 70.4 –Average value for the year 2019). Results The average cost per gamma knife radio surgery procedure was calculated to be US $2,469 (INR 1,73,832), with major costs attributed to machinery & equipment (43.6%), followed by manpower (32.5%), electricity (9.67%), equipment maintenance (8.61%) etc. The initial investment to establish a Gamma Knife facility is significantly higher with an MRI unit (Model A) at US $ 9,836,423 (INR 69,24,84,164) compared to one without (Model B) at US $7,294,986 (INR 51,35,66,988). Currently, the patient has to pay US $1,065 (INR 75,000) for a gamma knife radio surgery, which poses a challenge for achieving breakeven since the variable cost for the same is US $1,367 (INR 96,239) per procedure. Conclusion The study serve as a tool for strategic planning, pricing adjustments, and enhancing operational efficiencies, thus ensuring that such high-end technologies can be sustainably integrated into the public healthcare landscape of a developing country like India.